Meeting report: 34th international conference on antiviral research. (October 2022) - Brancale, Andrea; Carter, Kara; Delang, Leen; Deval, Jerome; Durantel, David; Gentry, Brian G; Jordan, Robert; Julander, Justin G.; Lo, Michael K.; Pérez-Pérez, Maria-Jesús; Schang, Luis M.; Seley-Radtke, Katherine L.; et al.
As a result of the multiple gathering and travels restrictions during the SARS-CoV-2 pandemic, the annual meeting of the International Society for Antiviral Research (ISAR), the International Conference on Antiviral Research (ICAR), could not be held in person in 2021. Nonetheless, ISAR successfully organized a remote conference, retaining the most critical aspects of all ICARs, a collegiate gathering of researchers in academia, industry, government and non-governmental institutions working to develop, identify, and evaluate effective antiviral therapy for the benefit of all human beings. This article highlights the 2021 remote meeting, which presented the advances and objectives of antiviral and vaccine discovery, research, and development. The meeting resulted in a dynamic and effective exchange of ideas and information, positively impacting the prompt progress towards new and effective prophylaxis and therapeutics.